Microstructural evolution of grain refinement in superalloy Inconel 718 during low temperature and slow strain rate hot compression - Wei Zhou; Kaixuan Chen; Yanlin Wang; Yuzhi Zhu; Junwei Qin; Yaya Zhao; Zidong Wang; Xiaohua Chen; Lingli Zuo (Journal of Materials Research and Technology, 2024)
This study explores the plastic deformation mechanism and microstructural evolution of as-homogenized and as-forging Inconel 718 alloy through low temperature and slow strain rate hot compression deformation. The stress-strain curves of Inconel 718 alloy were analyzed by modulating the deformation temperature, strain rate, and strain, and the extreme grain refinement process from cast billets (with abnormally coarse grains) to the final compression sample was revealed. The results show that the true stress levels are lower during both low temperature and slow strain rate hot compression, relative to high temperature and fast strain rate deformation. For the as-homogenized Inconel 718 sample, the same grain refinement as the high temperature and fast strain rate (i.e. forging deformation) was achieved by the low temperature and slow strain rate compression deformation. For Inconel 718 samples after forging, uniform, equiaxed, fine grains with an average size of 2.9 μm are obtained at lower deformation temperatures and slower strain rates. Based on these results this low temperature and slow strain rate metallic forming process demonstrates the potential for the application of plastic deformation in controlling grain size, morphology, and distribution, providing a direct, economical, and efficient approach to achieving fine equiaxed grain structures in as-forging metallic materials.